Examining the Impact of Customer Orientation and Service Quality on Customer Satisfaction: The Mediating Role of Service Quality - Aisyah Adini Putri; Puspita Chairun Nisa Baskara; Ika Baskara; Unggul Kustiawan Baskara (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to examine the influence of Customer Orientation and Service Quality on Customer Satisfaction in the context of Hisana fried chicken purchases. This quantitative research collected data through questionnaires distributed to 130 consumers who purchased Hisana fried chicken, using a purposive sampling technique. The data were analyzed using the Structural Equation Modeling - Partial Least Square (SEM-PLS) method to assess the relationships between variables. The results indicate that Customer Orientation has a positive effect on Customer Satisfaction, Customer Orientation positively influences Service Quality, and Service Quality positively affects Customer Satisfaction. However, Service Quality does not mediate the relationship between Customer Orientation and Customer Satisfaction. These findings provide insights for restaurants to enhance Customer Orientation and Service Quality as strategies to strengthen customer satisfaction.